Genetic Polymorphisms in Estrogen Metabolic Pathway Associated with Risks of Alzheimer's Disease: Evidence from a Southern Chinese Population. Issue 2 (19th January 2017) - Chen, Lu Hua; Fan, Yan Hui; Kao, Patrick Yu Ping; Ho, Deborah Tip Yin; Ha, Joyce Cheuk Tung; Chu, Leung Wing; Song, You‐Qiang
Abstract : Objectives: To investigate whether genetic variations on the estrogen metabolic pathway would be associated with risk of Alzheimer's disease (AD). Design: Cross‐sectional study. Setting: Individuals were recruited at the Memory Clinic, Queen Mary Hospital, Hong Kong. Participants: Chinese individuals with (n = 426) and without (n = 350) AD. Measurements: All subjects underwent a standardized cognitive assessment and genotyping of four candidate genes on the estrogen metabolic pathway (estrogen receptor α gene (ESR1), estrogen receptor β gene (ESR2), cytochrome P450 19A1 gene (CYP19A1), cytochrome P450 11A1 gene (CYP11A1)). Results: Apart from consistent results showing an association between apolipoprotein (APO)E and AD, strong evidence of disease associations were found for polymorphisms in ESR2 and CYP11A1 based on the entire data set. For ESR2, significant protective effects were found for A alleles of rs4986938 (permuted P = .02) and rs867443 (permuted P = .02). For CYP11A1, significant risk effects were found for G alleles of rs11638442 (permuted P = .03) and rs11632698 (permuted P = .03). Stratifying subjects according to APOE ε 4 status, their genetic effects continued to be significant in the APOE ε 4‐negative subgroup. Associations between CYP11A1 polymorphisms (rs2279357, rs2073475) and risk of AD were detected in women but not men. Further gene‐level analysis confirmed the above association between ESR2 and CYP11A1, and pathway‐level analysis highlighted the genetic effect of the estrogen metabolic pathway on disease susceptibility (permuted pathway‐level P = .03). Conclusion: Consistent with previous biological findings for sex steroid hormones in the central nervous system, genetic alterations on the estrogen metabolic pathway were revealed in the Chinese population. Confirmation of these present findings in an independent population is warranted to elucidate disease pathogenesis and to explore the potential of hormone therapy in the treatment of AD.